Contribution of Counseling in Building Clients' Ability to Adapt to the Community in Correctional Centers - Firdaus W Suhaeb; Ernawati S, K (Journal of Social Science and Economics (JOSSE), 2025)
The purpose of this study is to analyze the contribution of counseling services at the Correctional Center (Bapas) in supporting the social reintegration process of clients. As an institution that plays a crucial role in guiding inmates after their release from prison, Bapas has a responsibility to ensure that clients are able to function socially, psychologically, and economically in society. Counseling programs at Bapas are aimed at helping clients understand the social and legal consequences of criminal acts, change their life orientation, and improve the social skills necessary to adapt to their new environment. This study uses a literature review method with secondary data as the primary basis. Secondary data were obtained from various written sources, such as books, scientific journals, research reports, census results, and articles. An evaluation of the program's effectiveness indicates that the success of the service is strongly influenced by internal and external factors, such as client readiness, family support, the competence of the community counselor, the availability of facilities, and the responsiveness of the social environment. The study also reveals that structured, professional, and ongoing counseling and supervision can reduce the risk of recidivism and increase the chances of successful social reintegration. Thus, Bapas services play a strategic role in rebuilding clients' lives and strengthening social security in the community.